Surgical treatment of fourth branchial apparatus anomalies: a case series study - Wan-Xin Li; Yanbo Dong; Aobo Zhang; Jun Tian; Cheng Lu; Jean Pierre Jeannon; Liangfa Liu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Fourth branchial apparatus anomalies, are rare clinical entities, and present as complex cysts, sinuses and fistulae in the neck that can be difficult to manage. Methods This is a retrospective review of a series of consecutive patients with fourth branchial apparatus anomalies treated at Department of Otolaryngology Head and Neck Surgery, Beijing Friendship Hospital, Capital Medical University, from Apr 2014 to Nov 2019. Results Ten patients with fourth branchial apparatus anomalies were identified, including 8 patients with fourth branchial fistula, and 2 patients with fourth branchial pouch sinus. There were 6 female patients and 4 male patients. Their age was from 6 years old to 39 years old (average age 20.4 years old, median age was 21 years old). All 8 fistulae were on the left side, while 2 pouch sinuses were both on the right side. Pre-operative examination with fiberoptic laryngoscope, barium swallow X-ray, CT or MRI identified internal orifice at pyriform fossa apex in 8 (80%) patients. All patients underwent challenging surgical resection by the senior author. Intra-operative direct laryngoscope confirmed or identified internal orifice in 9 (90%) patients. The tracts were all followed to the vicinity of inferior cornu of the thyroid cartilage and the cricothyroid space. Complete resection of cervical lesions and their attachment to hypopharynx were achieved in 9 cases. No complication occurred. One recurrence was detected, in the only patient whose internal orifice could not be located pre- or intra-operatively, and the hypopharyngeal attachment could not be removed. Conclusions Direct laryngoscopy under general anesthesia is a reliable method of diagnosis for the fourth branchial apparatus anomalies. Complete surgical removal of fourth branchial apparatus anomalies, including their hypopharyngeal attachment, is the treatment of choice, and the key to prevent recurrence.